2014
DOI: 10.2147/ijn.s59338
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical studies of N3-O-toluyl-fluorouracil-loaded lipid-based nanosuspensions in H22-bearing mice

Abstract: Purpose N 3 -O-toluyl-fluorouracil (TFU) is a potential antitumor prodrug of 5-fluorouracil (5-FU), but its poor solubility has limited its use in clinic. This study aimed to improve the bioavailability of TFU by preparing TFU-loaded lipid-based nanosuspensions (TFU-LNS) and perform a preclinical evaluation. Methods TFU-LNS were prepared through high-pressure homogenization and were lyophilized afterwards. For in vitro test, the physicochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…43 Similar results have been reported in other studies. 30,44,45 After administration of sorafenib-LNS formulation, sorafenib was accumulated in liver to a considerable extent compared with other organs. The passive targeting of sorafenib-LNS to liver indicates the potential for an increased therapeutic effect on HCC and requires further investigation.…”
Section: Time-dependent Variation Of Sorafenib Levels In Tissuesmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Similar results have been reported in other studies. 30,44,45 After administration of sorafenib-LNS formulation, sorafenib was accumulated in liver to a considerable extent compared with other organs. The passive targeting of sorafenib-LNS to liver indicates the potential for an increased therapeutic effect on HCC and requires further investigation.…”
Section: Time-dependent Variation Of Sorafenib Levels In Tissuesmentioning
confidence: 99%
“…29 In our previous work, we prepared docetaxelloaded LNS and N3-O-toluyl-fluorouracil-loaded LNS by high-pressure homogenization, and both exhibited good antitumor activity and better tumor accumulation than the free drug, which suggested that LNS may be a promising drug delivery system for cancer therapy. 29,30 In this study, sorafenib-loaded LNS (sorafenib-LNS) were prepared by nanoprecipitation as an intravenous (IV) injectable formulation that we expected would increase the therapeutic efficiency and reduce gastrointestinal irritation. The particle size, zeta potential, and in vitro release properties of sorafenib-LNS were characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the nanoemulsion system incorporating OXA/DCK and 5-FU demonstrated a prolonged half-life for OXA and 5-FU, which was extended 5.68-and 1.82-fold, respectively, than the half-life after intravenously administration of OXA and 5-FU, suggesting prolonged therapeutic activity of the drug. 53,54 Like other platinum-based compounds, OXA exerts its cytotoxic effect mostly through DNA damage. Apoptosis of cancer cells can be caused by formation of DNA lesions, arrest of DNA synthesis, inhibition of RNA synthesis, and triggering of immunologic reactions.…”
mentioning
confidence: 99%